1998
DOI: 10.1007/s004300050080
|View full text |Cite
|
Sign up to set email alerts
|

Poor correlation between microimmunofluorescence serology and polymerase chain reaction for detection of vascular Chlamydia pneumoniae infection in coronary artery disease patients

Abstract: Chlamydia pneumoniae has been associated to coronary artery disease by various methods including recovery of viable bacteria from plaques. The pathogenetical relevance of this is unclear but investigation of antichlamydial therapy in coronary arteriosclerosis is already in progress. The microimmunofluorescence test (MIF), the only species-specific serological assay available, might be considered useful in identifying patients with vascular chlamydial infection. However, this has never been systematically exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…C. pneumoniae organisms were frequently detected in patients with no or low antibody titers and were often absent in the presence of high antibody titers (4,7,9,13,16,31,33,36,37,41,42,55,56,77). For Kuo and Campbell (34), "this remains an unsolved paradox with no good explanation.…”
Section: Detection Of C Pneumoniae In Atherosclerotic Arteries By Pcrmentioning
confidence: 99%
“…C. pneumoniae organisms were frequently detected in patients with no or low antibody titers and were often absent in the presence of high antibody titers (4,7,9,13,16,31,33,36,37,41,42,55,56,77). For Kuo and Campbell (34), "this remains an unsolved paradox with no good explanation.…”
Section: Detection Of C Pneumoniae In Atherosclerotic Arteries By Pcrmentioning
confidence: 99%
“…Serologic analyses are not useful for predicting carriage of C. pneumoniae in the vascular wall (84), but several investigators have reported that it is rare with a vascular C. pneumoniae infection in C. pneumoniae-seronegative adult individuals (9,82,84,112). Thus, at the best, serology may be used as a screening tool.…”
Section: Alternative Types Of Specimensmentioning
confidence: 99%
“…Since C. pneumoniae is difficult to culture, serological analysis still represents a routine approach for the diagnosis of C. pneumoniae infection. However, conflicting results have been published on the relationship between serology and the detection of the organism in atherosclerotic plaques (6,17), and Ericson et al reported no association between C. pneumoniae seropositivity and the degree of atherosclerosis (8).…”
Section: Vol 41 2003mentioning
confidence: 99%